2010
DOI: 10.1016/j.gloplacha.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of late Holocene climatic variability and land use change on the flood hydrology of the Guadalentín River, southeast Spain

Abstract: a b s t r a c t a r t i c l e i n f oThe Guadalentín River, located in southeast Spain, is considered one of the most torrential rivers in Spain, as indicated by catastrophic events such as the 1879 flood that caused 777 fatalities in the Murcia region. In this paper, flood frequency and magnitude of the upper Guadalentín River were reconstructed using geomorphological evidence, combined with one-dimensional hydraulic modelling and supported by records from documentary sources at Lorca in the lower Guadalentín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
83
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 42 publications
11
83
0
4
Order By: Relevance
“…Municipal Archive, of which 15 were classified as ordinary, 7 extraordinary and 9 167 catastrophic (Benito et al, 2010). During the second half of the 19th century, an 168 increase in frequency of extraordinary and catastrophic floods is reflected both in the 169 documentary record (with high economic losses and casualties) and in the 170 palaeoflood record (with high energy sedimentary structures).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Municipal Archive, of which 15 were classified as ordinary, 7 extraordinary and 9 167 catastrophic (Benito et al, 2010). During the second half of the 19th century, an 168 increase in frequency of extraordinary and catastrophic floods is reflected both in the 169 documentary record (with high economic losses and casualties) and in the 170 palaeoflood record (with high energy sedimentary structures).…”
mentioning
confidence: 99%
“…We consider our age control -historical records and radiocarbon for 586 the oldest sample T-17 (~1000 years) -sufficiently reliable to allow us to assign 587 calendar ages to individual flood events (Benito et al, 2010) and so derive expected 588 equivalent doses. 589…”
mentioning
confidence: 99%
“…scars on trees and tilting; Herget, 2012;Benito and Díez-Herrero, 2015). A number of studies have combined both historical and geological indicators to ascertain the magnitude and frequency of past flood, increasing the robustness of the frequency analysis of rare floods (Benito et al, 2010). This paper aims to describe the different techniques and approaches used in order to obtain quantitative information from historical flood data, as well as to draw attention to its different scientific and engineering applications.…”
Section: G Benito Et Al: Quantitative Historical Hydrology In Europementioning
confidence: 99%
“…Viglione et al (2013) demonstrated that the number of floods exceeding the perception threshold is more important than the uncertainty on discharge value A reduction on the error is obtained for a return period of the largest historical flood about twice length of the pre-instrumental record . Many documentary-based flood studies shown that flood frequency has been influenced by the internal variability of atmospheric circulation, with flood clusters at some time periods (Glaser et al, 2010), or by impacts on the environmental patterns such as land use (Benito et al, 2010) and engineering works (Machado et al, 2015). A simple test of stationarity for censored samples (systematic and/or non-systematic) was proposed by Lang et al (1999) assuming that the flood series can be described by a homogenous Poisson process (Naulet et al, 2005).…”
Section: Flood Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation